Integrated dynamic physiological model for drug infusion simulation studies - Montain, María Elisa (2014)
This work presents a dynamic model that integrates some of the main processes of the human physiology. It is aimed at simulating the behavior of most relevant variables in response to the administration of typical drugs used in medical procedures. The model integrates the following submodels available in the open literature: (i) cardiovascular, (ii) baroreflex, (iii) respiration, (iv) transport and distribution of substances, (v) pharmacological effects of drugs. The integrated model has a difficult mathematical structure due to the nonlinearity present in most relationships and the occurrence of time events associated with heart valves and other discontinuous phenomena. An efficient computational implementation was developed in the Fortran programming language and applied to several case studies. The results are in reasonable agreement with published experimental data although further studies are required to improve the model accuracy for real applications. The simulation model can be used as a computational tool for medical training and off-line diagnosis, as well as the basis for a patient specific online decision support system.